Secret Knowledge: Rediscovering the Lost Techniques of the Old Masters - Hockney, David -1937 (London Thames & Hudson, 2001)
Recently, David Hockney, often described as the "world's most popular artist," has made headlines not with his own work but with his sensational and controversial theories about how some of Western art's famous masterpieces – paintings by artists such as da Vinci, Caravaggio, Velázquez, and Van Eyck – were actually created. A chance observation of a drawing in London's National Gallery led Hockney to ask, "How was this done?"His answer led to fascinating insights into the history of art: that many of the world's most revered artists used mirrors and various optical devices – such as the camera obscura – to project images onto their canvasses and then "traced" the scenes. Hockney's radical speculations have prompted both astonishment and outrage from prominent art historians and museum directors worldwide. The debate aside, Secret Knowledge offers readers the exhilarating opportunity to see the Old Masters afresh?through the eyes of a living master.In Secret Knowledge, hundreds of paintings are reproduced in stunning color plates, and many are discussed in close and accessible detail. Hockney's own drawings and photographs illustrate how artists would have used the technology available to them in rendering their subjects. Extracts from historical and modern documents provide further evidence while correspondence between Hockney and an impressive array of international art historians, curators, and scientists details both the evolution of his theory and the furor that has erupted over it.
Keywords: Middle Ages (500-1400); Renaissance (1400-1600); 17th Century (1601-1700); Fine art